The relationship between parental phubbing and learning burnout of elementary and secondary school students: The mediating roles of parent-child attachment and ego depletion - He, Qingqing; Zhao, Bihua; Wei, Hua; Huang, Feng (Frontiers in Psychology, 2022)
In this study, we examined the effects of parental phubbing on learning burnout in elementary and secondary school students and its mechanism of action. A questionnaire method was applied to investigate parental phubbing, parent–child attachment, ego depletion, and learning burnout among 2090 elementary and secondary school students in Anhui Province, China. The results are as follows: (1) Parental phubbing was significantly correlated with parent–child attachment, ego depletion, and learning burnout; (2) Parental phubbing has an indirect impact on learning burnout in elementary and secondary school students through three pathways: a separate mediating effect on parent–child attachment, a separate mediating effect on ego depletion, and a chain mediating effect on both. Parental phubbing is a risk factor for Learning Burnout, which can positively affect Learning Burnout in elementary and secondary school students. The findings of the study contribute to revealing the influence mechanism of parental phubbing on learning burnout in elementary and secondary school students.